Una ausencia muy presente : la liberación en la vida cotidiana - Foster, Jeff (Editorial Kairós, 2010)
In this spiritual exploration, Jeff Foster argues that the concept of enlightenment is a myth and that liberation--far from being a goal within the reach only of spiritual masters and gurus--can be achieved by anyone, right at this very moment. Using everyday language and drawing on both personal experience and age-old wisdom, Foster argues that all seeking and longing of the mind can come to an absolute end by rejecting the notion of being a separate individual and immersing oneself into unconditional love--an immersion that will reveal the great secret in even the most ordinary of lives.